Psychometric properties of the New Ecological Paradigm (NEP) Scale in Serbian Sample - Vdović, Milica; Hagen, Mina; Simonović, Anja; Avramović, Nađa; Milošević-Đorđević, Jasna (Psihološka istraživanja, 2024)
Climate change is a growing threat to humanity and coping with its potentially disastrous effect will require widespread behavioural change at both societal and individual level. Theory and empirical research have emphasised the role of pro-environmental attitudes as antecedents of pro-environmental behaviour. Using a large community Serbian sample (N=871 of adult population) assessed with face to face interviews, we searched for the psychometric characteristics of the New Ecological Paradigm scale (NEP), a widely used instrument for assessing pro-environmental attitudes worldwide. The dimensionality of Dunlap’s NEP scale is frequently questioned, because studies revealed three, four, or only one dimension; therefore there is ongoing call for further validation. This was the first time that psychometric characteristics of the NEP scale have been tested on a large adult sample in Serbia with addition of testing its predictive power to explain environmental behaviour (using environmental behaviour questionnaire). The results of parallel analysis on the Serbian sample, pointed to the three factor structure: Human is (not)above nature; Ecological crisis; Human’s (non-)exception from nature, similar to the previous findings from the region. The three factor solution explained about half of variance. The factor ecological crisis emerged as the only significant predictor for the pro-environmental behaviour. Further analysis of the pro-environmental attitudes and behaviour is needed in order to better understand and communicate the importance and urgency for earth protection.